Heavy metals interact with the microbial community and affect biogas production in anaerobic digestion: A review. (15th June 2019) - Guo, Qian; Majeed, Sabahat; Xu, Rong; Zhang, Kai; Kakade, Apurva; Khan, Aman; Hafeez, Fauzia Yusuf; Mao, Chunlan; Liu, Pu; Li, Xiangkai
Abstract: Heavy metals (HMs), which accumulate in digestion substrates, such as plant residues and livestock manure, can affect biogas yields during anaerobic digestion (AD). Low concentration of Cu 2+ (0–100 mg/L), Fe 2+ (50–4000 mg/L), Ni 2+ (0.8–50 mg/L), Cd 2+ (0.1–0.3 mg/L), and Zn 2+ (0–5 mg/kg) promote biogas production, while high concentrations inhibit AD. Trace amounts of HMs are necessary for the activity of some enzymes. For example, Cu 2+ and Cd 2+ serve as cofactors in the catalytic center of cellulase and stimulate enzyme activity. High contents of Cd 2+ and Cu 2+ inhibit enzyme activity by disrupting protein structures. Trace amounts of HMs stimulate the growth and activity of methanogens, while high levels have toxic effects on methanogens. HMs affect the hydrolysis, acidification, and other biochemical reactions of organics in AD by changing the enzyme structure and they also impact methanogen growth. A better understanding of the impact of HMs on AD can provide valuable insights for improving the digestion of poultry manure and plant residues contaminated with HMs, as well as help mitigate HMs pollution. Although several studies have been conducted in this field, few comprehensive reviews have examined the effect of many common HMs on AD. This review summarizes the effects of HMs on the biogas production efficiency of AD and also discusses the effects of HMs on the activities of enzymes and microbial communities. Graphical abstract: Image 10243 Highlights: Heavy metals reduce cellulase activity by altering the enzyme spatial structure. Heavy metals inhibit methanogens growth and reduce their activities. Heavy metals have minor effects on pH and VFA concentration in anaerobic digestion.